Modelling landfill as a complex biophysical technology - Lowe, Martin (Cranfield University, 1998)
Concerns regarding climate change are becoming a driver behind legislation at both UK and EU levels, and also on the wider, planetary scale This is the case with emissions from landfills where the release of methane is being targeted for reduction This thesis uses an integrative approach, incorporating concepts of hierarchy from systems theory, to model landfill as a complex biophysical technology It assesses the contribution to carbon deposition and global warming of landfill through changes to that technology itself and through changes in the waste stream caused by potential waste policies The thesis develops an holistic, conceptual model of the landfill system, mapping flows and transformations of carbon within that system It further develops this conceptual model into a calculating model of landfill as a waste management technology incorporating measurements taken to provide new data and validate published data to calibrate the model It thus applies modelling techniques to a biophysical technology, producing an integrated model of the landfill that allows the knowledge gained from other research to be used to explore engineering and operational decisions on landfills The thesis includes results from measurements of the composition of household waste, and of the biochemical methane potential (BMP) of fractions of that waste It includes measurements of the residual BMP in samples of excavated waste and measurements of gas flows The main results suggest the following • Early capping of landfilled waste is important in reducing the global warming impact, • If the rate of degradation of the waste is accelerated in the drive towards sustainability, capping should be carried out even earlier if the global impact is not to be increased, • Although recycling parts of the degradable elements of the waste stream has the effect of reducing the global impact, extensive recycling has implications for landfill engineering